2023
DOI: 10.3390/vaccines11020287
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Closed Linear Epitopes in S1-RBD and S2-HR1/2 of SARS-CoV-2 Spike Protein Able to Induce Neutralizing Abs

Abstract: SARS-CoV-2 has evolved as several variants. Immunization to boost the Ab response to Spike antigens is effective, but similar vaccines could not enhance Ab efficacy enough. Effective Ab responses against the human ACE2 (hACE2)-mediated infection of the emerging SARS-CoV-2 variants are needed. We identified closed linear epitopes of the SARS-CoV-2 Spike molecule that induced neutralizing Abs (nAbs) against both S1-RBD, responsible for attachment to hACE2, and S2-HR1/2, in convalescents and vaccine recipients. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
1
0
0
Order By: Relevance
“…We introduce NmAbs against SARS-CoV-2 with linear epitope recognition specificity. In line with our results, a recent study reported mAbs with strong neutralizing activities directed to linear epitopes [ 44 ]. However, there are limited reports on the serological reactivity to "linear" immunodominant sites on the RBD [ 45 ].…”
Section: Discussionsupporting
confidence: 92%
“…We introduce NmAbs against SARS-CoV-2 with linear epitope recognition specificity. In line with our results, a recent study reported mAbs with strong neutralizing activities directed to linear epitopes [ 44 ]. However, there are limited reports on the serological reactivity to "linear" immunodominant sites on the RBD [ 45 ].…”
Section: Discussionsupporting
confidence: 92%